Clinical and mutational spectrum of Colombian patients with Pelizaeus Merzbacher Disease - Velasco-Parra, Harvy Mauricio; Maradei-Anaya, Silvia Juliana; Acosta-Guio, Johanna Carolina; Arteaga-Diaz, Clara Eugenia; Prieto-Rivera, Juan Carlos (Colombia Medica, 2018)
Pelizaeus Merzbacher Disease (PMD) is an X-linked developmental defect of myelination that causes a childhood chronic spastic encephalopathy. Its genetic aetiology can be either a duplication (or other gene dosage alterations) or a punctual mutation at the PLP1 locus. Clinically, it presents with developmental delay, nistagmus and spasticity, supported by neuroimaging in which the defect of myelination is evident. We present a series of 7 Colombian patients diagnosed with PMD, describing their genotypic and phenotypic characteristics and heterogeneity. We found PLP1 mutations in 71,5% of patients taken to molecular diagnosis and PLP1 duplications in the other 28,5%. We suggest that for Colombian population it might be better to start the confirmatory algorithm with full sequencing of the affected gene.